2021
DOI: 10.33448/rsd-v10i9.17817
|View full text |Cite
|
Sign up to set email alerts
|

O gênero Bacillus aplicado ao controle biológico de doenças de plantas

Abstract: Para atender à crescente demanda mundial por alimentos livres de resíduos químicos, muitos microrganismos vêm sendo utilizados como agentes de biocontrole de importantes fitopatógenos e pragas em culturas importantes comercialmente. O gênero Bacillus é amplamente utilizado para este fim, assim, objetivou-se neste artigo concentrar as principais atualizações sobre o gênero, levando em consideração aspectos biológicos, taxonômicos, genéticos e as aplicabilidades e potencialidades desse grupo de procariotos em aç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
0
3
0
2
Order By: Relevance
“…Figure 1C shows a linear graph showing that the higher the dose of B. subtilis, the higher the number of grains per pod, regardless of the stage at which it is applied. The bacterium acts by improving the absorption of water and nutrients and the production of antibiotics, phytohormones, and enzymes, providing growth promotion and biological control of phytopathogens, giving the plant greater resistance, and increasing the number of grains per pod (Melo et al, 2021). A different result was observed by Zucareli et al (2018) when they found that the application of Itafós (Brazilian phosphate Itafós has low reactivity, in addition to being less concentrated, with 23.2% total P2O5 and 5.5% P2O5 soluble in 2% citric acid) associated with inoculation with B. subtilis did not influence the number of grains per pod in the bean crop.This result can be explained by the effectiveness of B. subtilis in strengthening the plant defenses, improving nutrient absorption and growth as a result of increased nitrogen fixation and phytohormone synthesis, triggering an increase in metabolites that sensitize the root system to the external conditions of the environment, even providing greater plant capacity to absorb nutrients (Melo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1C shows a linear graph showing that the higher the dose of B. subtilis, the higher the number of grains per pod, regardless of the stage at which it is applied. The bacterium acts by improving the absorption of water and nutrients and the production of antibiotics, phytohormones, and enzymes, providing growth promotion and biological control of phytopathogens, giving the plant greater resistance, and increasing the number of grains per pod (Melo et al, 2021). A different result was observed by Zucareli et al (2018) when they found that the application of Itafós (Brazilian phosphate Itafós has low reactivity, in addition to being less concentrated, with 23.2% total P2O5 and 5.5% P2O5 soluble in 2% citric acid) associated with inoculation with B. subtilis did not influence the number of grains per pod in the bean crop.This result can be explained by the effectiveness of B. subtilis in strengthening the plant defenses, improving nutrient absorption and growth as a result of increased nitrogen fixation and phytohormone synthesis, triggering an increase in metabolites that sensitize the root system to the external conditions of the environment, even providing greater plant capacity to absorb nutrients (Melo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The bacterium acts by improving the absorption of water and nutrients and the production of antibiotics, phytohormones, and enzymes, providing growth promotion and biological control of phytopathogens, giving the plant greater resistance, and increasing the number of grains per pod (Melo et al, 2021). A different result was observed by Zucareli et al (2018) when they found that the application of Itafós (Brazilian phosphate Itafós has low reactivity, in addition to being less concentrated, with 23.2% total P2O5 and 5.5% P2O5 soluble in 2% citric acid) associated with inoculation with B. subtilis did not influence the number of grains per pod in the bean crop.This result can be explained by the effectiveness of B. subtilis in strengthening the plant defenses, improving nutrient absorption and growth as a result of increased nitrogen fixation and phytohormone synthesis, triggering an increase in metabolites that sensitize the root system to the external conditions of the environment, even providing greater plant capacity to absorb nutrients (Melo et al, 2021). Corroborating the report by Abhilash et al (2016), multifunctional microorganisms, when associated with the plant, can promote its growth and a series of other benefits through different mechanisms of action, being expressed at various stages of plant development and presenting positive results with a direct impact on yield as was observed in this study (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…The adoption of biocontrol agents can increase productivity, improve the phytosanitary status of plants, stimulate more sustainable food production, decrease the application of pesticides and reduce the costs involved in the process (Zou et al, 2021). Several studies have identified efficient antagonist microorganisms for biological control (Dornelas et al, 2017;Melo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Esses modos de ação são fruto da vasta produção de enzimas extracelulares e compostos tóxicos que fungos do gênero Trichoderma podem produzir e excretar. Essas enzimas são responsáveis por degradar a parede celular de outros organismos e muitos dos metabólitos liberados possuem atividade antimicrobiana (MELO, 1991;MENEZES;SOUZA, 1995).…”
Section: Trichoderma Spp : Visão Geral E O Biocontrole De Fitonematoidesunclassified